2014
DOI: 10.1128/aac.00093-14
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Is Active against Leishmania amazonensis: In Vitro Effect of Its Association with Amphotericin B

Abstract: Resveratrol is a polyphenol found in black grapes and red wine and has many biological activities. In this study, we evaluated the effect of resveratrol alone and in association with amphotericin B (AMB) against Leishmania amazonensis. Our results demonstrate that resveratrol possesses both antipromastigote and antiamastigote effects, with 50% inhibitory concentrations (IC 50 s) of 27 and 42 M, respectively. The association of resveratrol with AMB showed synergy for L. amazonensis amastigotes, as demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 61 publications
(94 reference statements)
2
40
0
2
Order By: Relevance
“…Resveratrol, a polyphenol found in black grapes and red wine that has many biological activities, in association with amphotericin B, showed synergy against L. amazonensis in vitro [35].…”
Section: Treatmentmentioning
confidence: 99%
“…Resveratrol, a polyphenol found in black grapes and red wine that has many biological activities, in association with amphotericin B, showed synergy against L. amazonensis in vitro [35].…”
Section: Treatmentmentioning
confidence: 99%
“…Quercetin (3), vincetoxicoside B (6), kaempferol (8), and (-)-epicatechin (9) showed synergistic antifungal activities with the FICI (fractional inhibitory concentration index) [16,17] values <0.5. A preliminary structure-activity relationship could be observed that free 3-OH was important for synergistic antifungal activity in flavonoids, because in the structure of compounds 4, 5, and 7, which showed no synergistic antifungal activity, 3-OH group was not free and linked by methyl or glycosyl.…”
Section: Resultsmentioning
confidence: 99%
“…39) It has been shown that different compounds affect the leishmanial cell cycle, some with characteristics suggesting the induction of incidental death, an apoptosis-like mechanism. 22,30,40) Therefore, we analyzed the effect of derivatives on parasite cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives 3k and 3p decreased 1.13-and 1.24-fold, respectively, cells in G2/M phase (Table 3). In a previous work published by our group 30) amphotericin B (0.1 µM) did not affect the cell cycle of the parasite.…”
Section: Fig 2 Role Of Thioureas On No Productionmentioning
confidence: 99%